Rationale for the choice of operations in esophageal leiomyoma. - V. V. Vasylkivskyi; V. G. Getman (Medičnì Perspektivi)
Operations on the esophagus occupy an important place in the surgery of the gastrointestinal tract, since this organ passes through three anatomical regions: the neck, thoracic and abdominal cavity. The main pathologies for surgical interventions arecongenital malformations, injuries, foreign bodies, burns and scarry strictures, neuromuscular diseases of the esophagus, hernia of the esophagus and reflux esophagitis, diverticula, acquired fistula, esophageal cancer, benign tumors and cysts. For the majority of these conditions clear recommendations on diagnosis and treatment have been developed. In the literature, there is no consensus on indications for conservative or surgical treatment of patients with esophageal leiomyoma and the type of surgical intervention: 1) resection of the esophagus 2) removal of the tumor with part of the wall; 3) enucleation of the tumor; 4) endoscopic removal. Mortality after resection of the esophagus or its wall with plastic is 13%, and after enucleation of leiomyoma – 2%. In our clinical study, the analysis of the performed operations on patients with leiomyoma of the esophagus was performed. The aim – to make a retrospective analysis of different types of surgical interventions in patients with esophageal leiomyoma performed in the thoracic departments of the National Cancer Institute, Kiev City Clinical Cancer Center, Kiev Clinical Hospital N 17, Zhytomyr Regional Hospital, Vinnitsa Regional Hospital. Retrospective evaluation of 66 patients with morphologically confirmed esophageal leiomyoma was made. The following types of imagining were performed in patients: radiological examination of esophagus with solution of barium sulphate and radiography, computed tomography of the chest (CTc), computed tomography angiography (CTA), magnetic resonance contrast-enhanced imaging (MRI TO). Instrumental methods: esophagogastroduodenoscopy (EGD) with biopsy, endoscopic ultrasound, endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNA). The type of surgical interventions: proximal gastrectomy (n=3); Garlock operation (n=2); Lewis operation (n=3), resection of the tumor with part of the esophageal wall (n=6); tumor enucleation (n=52). Complications after operations in the early period: postoperative bleeding - the source is not identified, failure of the esophageal wall seam. In the late postoperative period – esophageal pleural fistula in two patients and esophageal stenosis in one patient. Indication for removal of leiomyomas: severity of symptoms, tumor size more than 5 cm, multiple leiomyomas, transition onto the stomach, patient's persistent desire, increase of volume in dynamics, changes in mucosa over the mass. Indications for resection options for surgery: adhesion of the tumor with the mucosa for more than three centimeters, the inability to exclude the malignant process, the giant esophageal leiomyoma with the transition onto the stomach. Patients who underwent non-surgical operations had a shorter postoperative hospital stay, fewer complications and a better quality of life. According to our results, preoperative biopsy with intact mucosa is not informative, but also does not increase the number of perforations.